Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Can anybody please help me to evaluate the following product?

$$\prod_{n=2}^\infty\dfrac{n^3 - 1}{n^3 + 1} $$

share|cite|improve this question

closed as off-topic by Sami Ben Romdhane, TooTone, Claude Leibovici, Davide Giraudo, vonbrand Mar 4 '14 at 17:24

This question appears to be off-topic. The users who voted to close gave this specific reason:

  • "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – Community, TooTone, Claude Leibovici, Davide Giraudo, vonbrand
If this question can be reworded to fit the rules in the help center, please edit the question.

Calculate the first few partial products. You should spot a pattern not too far in. – Daniel Fischer Mar 4 '14 at 15:40
...please...? And what have you tried? – DonAntonio Mar 4 '14 at 15:43
This is a duplicate of this question. – robjohn Mar 8 '14 at 0:42

Notice $$\frac{n^3-1}{n^3+1}=\frac{(n-1)(n^2+n+1)}{(n+1)(n^2-n+1)}$$ and $(n+1)^2-(n+1)+1=n^2+n+1$. Therefore we have a telescoping product

$$\prod_{n=2}^\infty \frac{n^3-1}{n^3+1}=\frac{1\cdot \color{blue}{7}}{\color{red}{3}\cdot 3}\cdot\frac{2\cdot \color{blue}{13}}{\color{red}{4}\cdot \color{blue}{7}}\cdot \frac{\color{red}{3}\cdot \color{blue}{21}}{\color{red}{5}\cdot \color{blue}{13}}\cdots=\frac{1\cdot 2}{3}=\frac{2}{3}$$

If nervous about doing cancelling like this in an infinite product (which is a valid point!), do it carefully for the partial products and end up with the same.

share|cite|improve this answer

Note that $$ \frac{n^3-1}{n^3+1}=\frac{(n-1)(n^2+n+1)}{(n+1)(n^2-n+1)}=\frac{(n-1)}{(n+1)}\cdot\frac{\big((n+1)^2-(n+1)+1\big)}{(n^2-n+1)}. $$ We have $$ \prod_{n=2}^N\frac{n-1}{n+1}=\frac{1\cdot 2\cdots(N-2)(N-1)}{3\cdot 4\cdots N(N+1)}=\frac{1\cdot 2}{N(N+1)}, $$ while \begin{align} \prod_{n=2}^N\frac{n^2+n+1}{n^2-n+1}&=\prod_{n=2}^N\frac{\big((n+1)^2-(n+1)+1\big)}{(n^2-n+1)}\\&=\frac{\big((N+1)^2-(N+1)+1\big)}{2^2-2+1}=\frac{N^2+N+1}{3}, \end{align} and hence $$ \prod_{n=2}^N\frac{n^3-1}{n^3+1}=\frac{1\cdot 2\cdot(N^2+N+1)}{3\cdot N(N+1)}\to \frac{2}{3}, $$ as $N\to \infty$.

share|cite|improve this answer

Not the answer you're looking for? Browse other questions tagged or ask your own question.